DYSPHONIA IN PEDIATRIC PRACTICE: CAUSES AND METHODS OF TREATMENT - E. Yu. Radtsig; D. V. Degtyareva; N. V. Ermilova (Вопросы современной педиатрии)
Causes of dysphonia in children and adolescents vary from genetic syndromes, congenital defects, diseases of various organs and systems and to non-observance of hygiene or voice overstrain. Complex examination can help to reveal such causes. Laryngeal endoscopy remains one of the most reliable methods of investigation, but non-invasive methods (acoustic voice analysis — AVA, electroglottography — EGG) are no less important. The more detailed specification of voice timbre disturbances (organic or functional, with psycho-emotional lability being the most common cause) can help choose the method of its correction. Complex homeopathic drugs are promising in treatment of dysphonia of various etiology in children. Aim: to assess reliability of non-invasive methods of voice examination (AVA and EGG) in treatment of functional dysphonia in children. Patients and methods: 100 patients with dysphonia aged from 3 to 15 years old were examined. All of them were performed laryngeal endoscopy, AVA and EGG. Results: both methods demonstrated reliable differences of characteristics, describing the quality of voice before and after the treatment. Conclusions: AVA and EGG reflect changes in voice quality during and after provided treatment (including complex homeopathic drugs) and can be used as unbiased criteria of treatment efficacy assessment.